2010
DOI: 10.4236/jbise.2010.32018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of deformation rate on the mechanical properties of arteries

Abstract: Pig aorta samples were tested uniaxially and equi- biaxially at deformation rates from 10 to 200 %/s. Under uniaxial and biaxial testing, loading forces were reduced up to 20% when the deformation rate was increased from 10 to 200 %/s, which is the opp- osite to the behaviour seen in other biological tissues. A rate-dependent isotropic hyperelastic constitutive equation, derived from the Mooney-Rivlin model, was fitted to the experimental results (e.g. aorta specimens) using an inverse finite element technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…Though some have used a cruciform specimen [18] or different types of clamping methods, care should be taken when comparing results obtained under different testing conditions, since geometry and boundary conditions may significantly alter the mechanical response observed in a biaxial test [32, 33]. …”
Section: Experimental Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Though some have used a cruciform specimen [18] or different types of clamping methods, care should be taken when comparing results obtained under different testing conditions, since geometry and boundary conditions may significantly alter the mechanical response observed in a biaxial test [32, 33]. …”
Section: Experimental Methodsmentioning
confidence: 99%
“…Square specimen shape is certainly the most common for biaxial testing of biological soft tissue, although some tests on cruciform specimen of pig arteries have also been reported [18]. …”
Section: Specimen Preparation and Preliminary Operationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hysteresis loops may be used to estimate damping capacity, which is associated with the ratio of the dissipated energy to the stored energy [69] . An interesting study on strain-rate effect of mechanical properties by Delgadillo et al [70] revealed that at a stretch ratio of 1.5, the experienced load within the arterial wall is reduced by 20% when the strain rate is increased from 10 to 200 %/S. They suggested that: "this behavior might be a consequence of the faster fluidization and small re-solidification that occurs in the cell at higher deformation rates".…”
Section: Viscoelastic Modellingmentioning
confidence: 99%